Pneumococcal conjugate vaccine use in adults. (3rd March 2016) - Isturiz, Raul E.; Schmoele-Thoma, Beate; Scott, Daniel A.; Jodar, Luis; Webber, Chris; Sings, Heather L.; Paradiso, Peter
ABSTRACT: Streptococcus pneumoniae is a leading cause of illness and death in adults. A polysaccharide vaccine has been available for over 30 years, but despite significant use, the public health impact of this vaccine has been limited. The 13-valent pneumococcal conjugate vaccine (PCV13) has been licensed by the US Food and Drug Administration and other international regulatory authorities with the assumption that induction of a T cell–dependent immune response and noninferior immunogenicity to vaccine antigens when compared with the polysaccharide vaccine would be important to satisfy a significant unmet medical need. PCV13 efficacy against vaccine-type pneumococcal community-acquired pneumonia was confirmed in a large randomized controlled trial in older adults and its use is now increasingly recommended globally.